Publication Review. Issue 1 (1st April 2014) - Cummings, Keith
LINKS: Australian Glass and the Pacific Northwest, Vicki Halper (ed.) (2013) Tacoma, WA, USA: Museum of Glass and Seattle and London: University of Washington Press, 180pp., ISBN: 978-0-295-99265-5, h/bk, £42.00